Miracles and Methods - Ravnå, Per-Bjarne (Biblical theology bulletin, 2021)
Prominent scholars in the field of historical Jesus research have argued that historians should be willing to accept all sorts of miracles that are convincingly attested to in the sources. The present article agrees with this view in principle but argues that, if analysed with the ordinary source-critical methods of conventional historical scholarship, there are significant and systematic differences in the source-critical strength of the stories. Miracles that fit inside a modern scientific worldview seem to have a stronger foundation in the sources than miracles that do not. The difference is quite clear when one compares the stories about how Jesus raised the dead, but it is also visible when one compares stories of other miracles. There are at least two ways of explaining these differences. One is that they are created by the scepticism of the modern scientific worldview of this writer. The other is that the differences exist in the sources because some of the miracle stories go back to memories of real events, while others do not.